Create Successful Content Media as Crisis Mitigation in Tourism Industry During Covid-19 Pandemic - Janette Maria Pinariya; Wulan Yulianti; Jane Mitha; Past Novel Larasaty (Ikatan Sarjana Komunikasi Indonesia, 2020)
Every year the Indonesian tourism industry continues to be managed optimally until finally, it can play a role in the country's foreign exchange earnings. Bank Indonesia (BI) stressed the importance of the tourism sector for the Indonesian economy as it succeeded in becoming the second major foreign exchange earner. However, with the Covid-19 pandemic casting a shadow on tourism industry, even online travel management that has utilized technology is experiencing a crisis. This study uses a descriptive qualitative research approach by collecting data through observation, book documentation and interviews to examine the effect of Covid-19 pandemic on tourism industry. This study found that in a crisis situation, it is very important for tourism industry to create successful content as crisis mitigation in tourism industry during theÂ Â Covid-19 pandemic. It is also necessary to conduct the four stages as framework of a human driven process (facilitated by technology) to close the gap. The essential insights into the importance of mitigating the perceived risk factors currently influencing tourism, particularly within the short to medium term, hence providing tourism marketers impetus to seek to address the current evolving consumer trend(s) related to the Covid-19 pandemic. It is really important that the message reflects empathy for what had happened.